Endless roads : roadtrip in Spain with the longboard girls crew - Rayos, Juan; Longboard Girls Crew; Sector 9 (Firm); FeelSales (Firm) ([Madrid] : Sector 9, 2011)
A group of girl skaters traveling in a van around Spain looking for places to skateboard. "15 days, 4,300 kilometers, 7 girls, 20 longboards and lots of fun. Because this is what it's all about: freedom, life, friendship and of course... skating!" --
"This is the visual chronicle of a roadtrip around Spain."
Originally released as a motion picture in 2011.
In English and Spanish; with Spanish subtitles for English dialogues, and subtitles in English for Spanish dialogues.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 25, 2016).
Keywords: Women skaters -- Spain; Skateboarders -- Spain; Spain -- Description and travel; Documentary films; Sports films; Nonfiction films; Road films; Internet videos; Streaming video